Testing the activation–orientation account of spatial attentional asymmetries using transcranial direct current stimulation - Loftus, Andrea; Nicholls, M. (Pergamon, 2012)
The general population shows an attentional bias to the left, known as pseudoneglect. This bias is thought to be driven by higher levels of activation in right parietal areas. Using transcranial direct current stimulation (tDCS) to manipulate activation, this study examined whether tDCS over the left and right posterior parietal cortices (PPC) affects pseudoneglect. Normal participants received tDCS over the left or right PPCs (15 in each group). Pseudoneglect was measured using the greyscales task, which requires a forced-choice discrimination of luminance between two opposing luminance gradients. The greyscales task was administered both before and after; (a) anodal (b) cathodal and (c) sham tDCS. Participants who received tDCS over the left PPC demonstrated pseudoneglect for the greyscales task, which was significantly reduced by anodal tDCS, but was unaffected by sham or cathodal tDCS. In contrast, for those participants who received right PPC tDCS, pseudoneglect for the greyscales task was unaffected by tDCS. Anodal tDCS, which is known to elevate neural excitation, may have overcome lower levels of activation in the left PPC, resulting in decreased pseudoneglect. These findings provide convincing evidence in support of an activation–orientation model of pseudoneglect and have implications for models of left neglect.